Pengaruh Kompetensi Digital dan Pelatihan Teknologi Informasi terhadap Kinerja Pegawai di Lingkungan Kementerian Kominfo - Muhammad adlan; Muhamad Rifki; IIma Syahrani Andriani (PT. Pustaka Cendekia Publisher, 2025)
This study aims to analyze the influence of digital competence and information technology training on employee performance within the Ministry of Communication and Information Technology (Kominfo). Digital competence plays a critical role in enhancing work effectiveness, particularly in the era of ongoing digital transformation. The research adopts a quantitative approach using survey methods, with data collected through questionnaires distributed to Kominfo employees. The findings indicate that both digital competence and IT training have a positive and significant impact on employee performance. These results highlight the importance of improving digital skills and continuous training to enhance productivity and the quality of public service in the government sector.